Let's solve your equation step-by-step.
<span><span><span><span>4<span>x^2</span></span>+<span>28x</span></span>−32</span>=0
</span>Step 1: Factor left side of equation.
<span><span><span>4<span>(<span>x−1</span>)</span></span><span>(<span>x+8</span>)</span></span>=0
</span>Step 2: Set factors equal to 0.
<span><span><span>x−1</span>=<span><span><span>0<span> or </span></span>x</span>+8</span></span>=0
</span><span><span>x=<span><span>1<span> or </span></span>x</span></span>=<span>−<span>8</span></span></span>
Is this multiplying or what??? Anyways try calculating those numbers so basically you need to calculate 28x2 or if you have to divide them or multiply them you would get the answer is very simple
<em>Correct answer is C). 6X+11</em>
Step-by-step explanation:
The given function f(x)= ![\frac{24x^{2} +63x + 34 }{4x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B24x%5E%7B2%7D%20%2B63x%20%2B%2034%20%7D%7B4x%2B3%7D)
On simplying the function f(x),
f(x)= ![\frac{6x(4x+3) -18x +63x + 34 }{4x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B6x%284x%2B3%29%20-18x%20%2B63x%20%2B%2034%20%7D%7B4x%2B3%7D)
f(x)= ![\frac{6x(4x+3) +45x + 34}{4x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B6x%284x%2B3%29%20%2B45x%20%2B%2034%7D%7B4x%2B3%7D)
f(x)= ![\frac{6x(4x+3) +11(4x+3)+x-33 + 34 }{4x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B6x%284x%2B3%29%20%2B11%284x%2B3%29%2Bx-33%20%2B%2034%20%7D%7B4x%2B3%7D)
f(x)= ![\frac{6x(4x+3) +11(4x+3)+x+1}{4x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B6x%284x%2B3%29%20%2B11%284x%2B3%29%2Bx%2B1%7D%7B4x%2B3%7D)
f(x)=![(6x+11)+\frac{(x+1)}{4x+3}](https://tex.z-dn.net/?f=%286x%2B11%29%2B%5Cfrac%7B%28x%2B1%29%7D%7B4x%2B3%7D)
From above equation
"(6x+11)" is Oblique asymptote and
is vertical asymptote
Therefore, Correct answer is C). 6X+11
I think it would be the last one 36